2019
DOI: 10.4103/jfmpc.jfmpc_208_18
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for involvement of private doctors in RNTCP – Qualitative study from Kerala, India

Abstract: Introduction: Engaging the private sector effectively has been considered as the single most important intervention required for Revised National TB Control Program (RNTCP) to achieve the overall goal of universal access and early detection. This study attempts to identify the barriers and facilitators in the involvement of private practioners in signed schemes of RNTCP. Materials and Methods: Six focus group discussions - four among private sector doctors and two among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…In 2016, even after the NTEP implemented a daily anti-TB regimen—the absence of which was cited as the major reason by the private sector for not participating—there was not much improvement in the private sector participation in terms of contributions towards TB notification or partnering with NTEP on signed partnership schemes. Operations researches conducted through the NTEP mechanisms, revealed many challenges for sub-optimal private sector participation [ 32 , 33 ]. Efforts were also put in place to understand the real problems of patients reaching the private sector [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, even after the NTEP implemented a daily anti-TB regimen—the absence of which was cited as the major reason by the private sector for not participating—there was not much improvement in the private sector participation in terms of contributions towards TB notification or partnering with NTEP on signed partnership schemes. Operations researches conducted through the NTEP mechanisms, revealed many challenges for sub-optimal private sector participation [ 32 , 33 ]. Efforts were also put in place to understand the real problems of patients reaching the private sector [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In India, PC‐level information on private sector performance can help secure the support of elected representatives for scaling up successful experiences and ensuring the sustainability of private sector involvement. There is evidence to suggest that instead of a centrally administered uniform model, services may be decentralised to develop locally appropriate models of partnerships with private providers [ 25 ]. PCs with adequate private sector notification can serve as role models for neighbouring constituencies.…”
Section: Discussionmentioning
confidence: 99%
“…Even after NTEP implemented a daily anti-TB regimenthe absence of which was the major reason the private sector cited not participating-there was not much improvement in the private sector participation. 17 Operations research identified several important barriers to engagement of the private sector in NTEP: absence of mutual trust between the public and private sector, concerns over patient confidentiality and patient choices, apprehension of losing patients, lack of consideration for hospital management, lack of time for doctors to document, inability of the program to keep commitments and timely payments, poor recognition of the private sector, and bureaucratic hurdles. 17 A recent study from Kerala of the prescribing pattern of practitioners reported that TB management in the private sector follows a reasonable standard of care in terms of treatment prescriptions.…”
Section: Tb Elimination Strategies In Keralamentioning
confidence: 99%
“…17 Operations research identified several important barriers to engagement of the private sector in NTEP: absence of mutual trust between the public and private sector, concerns over patient confidentiality and patient choices, apprehension of losing patients, lack of consideration for hospital management, lack of time for doctors to document, inability of the program to keep commitments and timely payments, poor recognition of the private sector, and bureaucratic hurdles. 17 A recent study from Kerala of the prescribing pattern of practitioners reported that TB management in the private sector follows a reasonable standard of care in terms of treatment prescriptions. 18 A private tertiary care center in Kerala demonstrated that establishing a management system within the hospital ensured 100% TB notification with a 4-fold increase over 6 months.…”
Section: Tb Elimination Strategies In Keralamentioning
confidence: 99%